Influence of the Nb Content on the Microstructure and Phase Transformation Properties of NiTiNb Shape Memory Alloys - Dagdelen, F.; Balci, E.; Qader, I. N.; Ozen, E.; Kok, M.; Kanca, M. S.; Mohammed, S. S. (Springer, 2020)
NiTi shape memory alloys (SMAs), as smart materials, are broadly used in medical implants and appliances despite the presence of toxic Ni. In this study, NiTiNb alloys were produced using the substitution of biocompatible Nb instead of Ni. The arc-melting method was utilized to make five SMA samples comprising Ni(29-x)Ti50Nb(21+x) (x = 0, 1, 2, 3, and 4); then, the phase transformation temperatures, microstructures, crystal structures, and chemical compositions were investigated by DSC, optical microscopy, XRD, and EDX measurements, respectively. The DSC results showed that the samples had a wide hysteresis with the B19 '<-> B2 phase transformation and martensite start temperatures below room temperature, which makes them suitable for superelastic implants. The presence of dissolved Nb in the matrix of the alloys was the main reason for the widening of temperature hysteresis. When the XRD and SEM results were examined, the beta-rich, B2, B19 ', and Ti2Ni phases were observed in all samples. Additionally, the main constituent in the dendritic microstructures was Nb.
Keywords: Mechanical-Properties; Temperature; Behavior; Oxidation